Bhutan : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bhutan. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that Bhutan continued to make strides in raising per capita incomes and reducing poverty as it concluded the 11th Five Year Plan in 2018. Notably, poverty declined from 12 percent in 2012 to 8.2 percent, and extreme poverty fell to just 1.5 percent. The country is poised to transition to middle-income status, with per capita incomes at nearly USD 3,600 in 2018, up from USD 1,100 in 2004. Growth has remained robust, averaging 6 percent over the 11th Plan. In FY2018, growth is expected to slow to 5.8 percent from 7.4 percent in FY2017, reflecting slowing construction activity of hydropower projects set to come on stream in 2018 and beyond.